Confronting gender inequality in a business school. Issue 5 (2nd September 2016) - Reilly, Amanda; Jones, Deborah; Rey Vasquez, Carla; Krisjanous, Jayne
ABSTRACT: This study, set in a New Zealand Business School, takes an integrative view of the university as an 'inequality regime' Acker, J. (2006b ). Inequality regimes: Gender, class and race in organizations. Gender and Society, 20(4), 441–464 including all types of women staff: academic women in permanent positions, academics on casual contracts and administrative staff. This approach contrasts with most studies of gender in higher education, which focus on academics, and often on the most senior academic roles. The business school, too, is under-researched in the literature of gender and higher education and we argue that these institutions constitute a particularly 'chilly climate' for women. The project discussed here was designed as participatory action research, but we found both participation and action difficult to accomplish. We reflect on how these difficulties resonate with the wider problem of confronting gender inequality in a 'chilly climate', and ask why further change is hard. We collected primary data from focus group interviews and a survey, and critically reflected on the process of data collection. Secondary data, including university reports and policies and national legislation, were also collected as part of the context of the School inequality regime. We analysed our data using Acker's categories: the 'visibility of inequality', the 'legitimacy of inequality' and 'mechanisms of control and compliance'. We found barriers to change both within and beyond the Business School itself. These included the low organisational priority given to gender equality, which in turn reflected a weak external regulatory environment. At the same time we found a lack of solidarity between women within the School, which we attributed partly to class-based differences. Organisational activism is difficult in this context, where gender inequality is both invisible and legitimated, reflecting a post-feminist mood of 'gender fatigue'.